2023
DOI: 10.1186/s12893-023-02085-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of total psoas muscle index for postoperative physical functional decline in older patients undergoing emergency abdominal surgery

Abstract: Background Older individuals increasingly require emergency abdominal surgeries. They are susceptible to surgical stress and loss of independence in performing daily activities. We hypothesized that the psoas muscle volume would be significantly associated with postoperative functional decline (FD) in older patients undergoing emergency abdominal surgery and aimed to evaluate the use of the psoas muscle volume on computed tomography (CT) scans. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Although this study found that chronological age is statistically associated with postoperative physical function decline, functional decline cannot be predicted using age alone [ 30 ]; frailty, defined as a decrease of physiological reserve, is a greater risk factor for functional decline than age [ 31 ]. Several tools exist to identify frailty in emergency cases, and in a simplified approach, previously, we revealed that low psoas muscle volume predicted early postoperative functional decline [ 32 ]. In addition, recent studies have shown that the use of laparoscopy in emergency abdominal surgery demonstrates a significant reduction in mortality in frail older patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this study found that chronological age is statistically associated with postoperative physical function decline, functional decline cannot be predicted using age alone [ 30 ]; frailty, defined as a decrease of physiological reserve, is a greater risk factor for functional decline than age [ 31 ]. Several tools exist to identify frailty in emergency cases, and in a simplified approach, previously, we revealed that low psoas muscle volume predicted early postoperative functional decline [ 32 ]. In addition, recent studies have shown that the use of laparoscopy in emergency abdominal surgery demonstrates a significant reduction in mortality in frail older patients [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in muscle volume can lead to limitations in ADL and a decline in quality of life [27,28]. Low muscle volume predicts poor clinical outcomes in various diseases [12][13][14]. One study reported an association between skeletal muscle mass and mortality of patients with critical illness [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…However, measurable parameters early in ICU admission have not been clearly validated to assess the risk of PICS. In various settings, skeletal muscle mass has been associated with various outcomes, including physical function [12][13][14]. One study revealed that the skeletal muscle mass of patients with critical illness is associated with mortality and ventilation-free days [15][16][17].…”
Section: Introductionmentioning
confidence: 99%